Teachers as a panopticon for smart class students during distance learning - Eka Rizki Rahmawati; Tuti Budirahayu (Department of Sociology, Faculty of Social and Political Sciences, Universitas Airlangga, 2021)
The education sector is experiencing the impact of the COVID-19 pandemic, resulting in the implementation of the distance learning (PJJ) system to reduce the risk of virus transmission. This system, however, has several obstacles, including the internet network, social inequality, uncertainty in choosing the appropriate learning method, and the decline in student achievement. This problem is also faced by smart class students at Hang Tuah Senior High School 2 of Sidoarjo, forcing its teachers to be able to create innovative learning and act actively to discipline their students. This study aimed to determine the teachers’ role as a panopticon for smart class students during distance learning. The qualitative research method was implemented using Foucault’s genealogical approach and the research informants were determined using the snowball technique. The results of this study reveal that the teachers’ role as a panopticon for the students is carried out with a hierarchical observation, giving reward and punishment, and repeated test system. This study concludes that the role of the teachers as a panopticon during distance learning at Hang Tuah Senior High School 2 of Sidoarjo is particularly useful for disciplining smart class students to carry out their obligations and prevent a decline in academic achievement even though the activities are done virtually.